1996
DOI: 10.1136/jcp.49.4.290
|View full text |Cite
|
Sign up to set email alerts
|

Single-tube nested PCR in the diagnosis of tuberculosis.

Abstract: Aims-To evaluate the usefulness of a single-tube nested polymerase chain reaction (PCR) assay in the diagnosis of tuberculosis in 1497 pulmonary and 536 extrapulmonary specimens. Methods-A single-tube nested PCR, utilising two sets of primers with different melting temperatures (88'C for external primers; 70°C for internal primers) to augment sensitivity and specificity without increasing the risk of amplicon contamination, was evaluated. Specimens were initially tested for the repetitive IS6110 sequences and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 19 publications
0
31
0
Order By: Relevance
“…The reasons for the false positive results could be cross contamination during the initial handling or an amplicon carry over contamination, which can be overcome by using a single tube nested PCR [18]. It was also found that the use of dUTP/Uracil-N-glycosylase could decrease the amplicon contamination [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reasons for the false positive results could be cross contamination during the initial handling or an amplicon carry over contamination, which can be overcome by using a single tube nested PCR [18]. It was also found that the use of dUTP/Uracil-N-glycosylase could decrease the amplicon contamination [18].…”
Section: Discussionmentioning
confidence: 99%
“…the reasons for the Lower Sensitivity may be many: Firstly, the presence of PCR inhibitors which are found to be more associated with the extrapulmonary specimens as compared to the pulmonary specimens [18][19]. A better extraction procedure like an immunomagnetic separation technique may be used to capture all the M. tuberculosis DNA, but not the inhibitors [18].…”
Section: Possible Tbm: (I) Clinical Criteria (A)mentioning
confidence: 99%
See 1 more Smart Citation
“…Single colonies were picked and suspended in PBS to reach approximately a 0.5 McFarland standard, and 10-fold dilutions were made. Viable counts were simultaneously made as previously published (9). Sputum samples known to be negative for any of the Burkholderia species tested were pooled and homogenized using 0.1% dithiothreitol in PBS (Sputasol) at room temperature for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…The few studies which have evaluated PCR for the diagnosis of extrapulmonary TB have included a high percentage of human immunodeficiency virus (HIV)-seropositive patients. The sensitivity of PCR in these studies ranges 42-93% [3][4][5][6]. Previously, we and others showed that PCR can be used for the detection of pulmonary TB cases in routine laboratories [7][8][9].…”
Section: Aamentioning
confidence: 99%